Manufacturing Competitiveness In Asia. - Jomo, K. S. (RoutledgeCurzon, 2003)
There are competing theories to explain the reasons behind the international competitiveness of manufacturing in Asia. Analysing these different theories will bring important lessons, not just for Asia, but for developing economies the world over. This lucid book studies industries and firms in East Asia and examines the major determinants of their economic performance.